Effect of Strategic Thinking on Performance of Non-Governmental Organizations in Northern Region of Kenya, Kenya - Thomas, Amoni Ngimoe; Gichana, Atandi Fred; Okwemba, Emily (Journal of Business and Strategic Management, 2025)
Purpose: This study investigates how strategic thinking influences the performance of NGOs in Northern Kenya, with a specific focus on how the dimensions of creativity, analysis, and decision-making significantly enhance NGO effectiveness. Methodology: Employing a mixed-methods approach, data were collected through structured questionnaires from 166 NGO leaders across the region and semi-structured interviews with 15 key informants. Stratified random sampling ensured diverse representation. Quantitative data were analyzed using descriptive statistics, correlation, and regression analyses, while qualitative data underwent thematic analysis. Findings: Results indicate a strong positive relationship between strategic thinking and NGO performance (r = 0.598, p < 0.001), with strategic thinking accounting for 35.8% of performance variance (R² = 0.358). Specifically, creativity and analytical decision-making emerged as critical dimensions. Qualitative insights highlighted the importance of contextual adaptation and cultural sensitivity. Unique Contributions to Theory, Policy and Practice: The findings contribute to strategic leadership theory, emphasizing the need for contextually adaptive practices in resource-constrained environments. Policy recommendations include capacity building in strategic thinking and fostering organizational cultures conducive to innovation and flexibility.